Effect of Antihistamines (Fexofenadineand Chlopheneramine) on activity some hepatical enzymes by using fertilized hens eggs embryos as a model - SihamAgmeeWadee; Mohammad Kailed Shindala (Tikrit Journal of Pure Science, 2023)
The aim of the present study was to investigate the effect of antihistamines(Chlorpheneramineand Fexofenadine) on (alkaline phosphatase, aspartate amino transpherase and alanine amino transferase) in tissue of fertilized hens eggs embryos as indicator to tissue damage. The injection of fertilized hen's eggs with antihistamines Fexofenadine at 12th day of incubation in  doses (0,5,0,1mg/ egginto air sell)after 24 hour of treatment induce significantly decrease in tissues activity of alkaline phosphatase (ALP),aspartate amino transpherase (AST) and alanine amino transferase (ALT) compared with control group in adose-dependent manner.Ingection of Chlorpheneramineat dose (0,5,0,1 mg/egginto air cell)induce  significantly decrease in tissues activity ofalkaline phosphatase  and aspartate amino transpherase compared with control group, but no significant decrease in tissue activity of  alanine amino transpharase(ALT)at dose(0,5,0,1mg/egg) compared with control group.Compare the effect of ChlorpheneramineandFexofenadine on some biochemical parameters, chlorpheneramine cause significan decrease intissues activity of alkaline phosphatase (ALP) and alanine amino transferase (ALT) larger than the group which terated withfexofenadine in the same dose, also chlorpheneramine cause significan decrease intissues activity of aspartate amino transferase larger than the group which treated with fexofenadine in same dose.We conclode the antihistamines hasharmful effects to tissueschick embryorepresented by the changes in activity of some biochemical parameter which its consider as a marker for damage this tissue